Analysis of Economic Inequality In Banyuwangi Regency - Yeni Puspita; Galih Wicaksono; Edy Wahyudi (MediaTrend, 2022)
Banyuwangi Regency is one of the regencies in East Java that has a higher economic growth rate than East Java's economic growth. Likewise, the poverty rate in Banyuwangi in 2019 was 7.52 percent, this figure is much lower than the East Java Province average of 10.2 percent (Central Statistics Agency, 2019). Poverty in Banyuwangi Regency is contributed by several sub-districts, namely Kalibaru, Licin, Songgon, and Glenmore, where the percentage of poverty is above 10%, while other sub-districts such as Giri, Tegaldimo, and Sempu the percentage of the number of poor people is below 6%. This indicates the occurrence of economic inequality, where there are vertical and horizontal differences that cause disparities or uneven development. This study aims to see how the economic inequality in Banyuwangi Regency. The method used in this research is descriptive qualitative. The object of this research is all sub-districts in Banyuwangi Regency. The data is obtained by distributing questionnaires and conducting interviews with the Office which is directly related to indicators of economic inequality. The results of the study found that there were several sub-districts that still lacked the availability of health facilities and educational facilities, the Stunting Rate was still high in some sub-districts, the distribution of UMKM in the Banyuwangi district was evenly distributed, and there were several sub-districts whose UMKM had not yet developed, the number of unemployed was still scattered in several districts, The provision of social assistance still has the problem of mistargeting so that the achievement of the goal of social assistance is not achieved.